Avaliação da vida útil de inserto para usinagem do aço microligado DIN 38MnVS6 pelo controle de resfriamento após forjamento a quente - Goulart, Guilherme Oliveira (2023)
Machining process parametrizations are widely studied and widespread. Research pursue to establish correlation between machining forces, tool wear, and cutting cooling fluid efficiency with operational parameters such as feed rate, depth of cut, and cutting speed, as well as with metallurgical characteristics of the material such as microstructure and hardness. This works aims to determine the best cooling condition after the hot forging process of DIN 38MnSV6 microalloyed steel to improve tool life during machining. Samples with 36,51 mm diameter and 160 mm length were extracted from hot-rolled cylindrical bars, heated in a resistive furnace at 1.220 °C, held for 28 minutes until complete thermal homogenization, and hot-forged in an universal test machine with compression rate of 4,7 %/min (conforming speed of 7.5 mm/s), to simulate industrial conditions. Different cooling rates of 0.8 °C/s, 1.0 °C/s, 1.8 °C/s and 2.9 °C/s after hot forging were investigated. After forging process, samples were machined with the following parameters: 0,2 mm/rev feed rate, 130 m/min cutting speed and 0,5 mm depth rate. Correlations between the wear level VB with cooling rates applied in the samples will be attained. To understand wear mechanism(s), microstructure, grain size, and fiber orientation of the samples after machining were analyzed, as well as features such as hardness, superficial roughness tensile testing responses after machining. The results showed that rupture limit tensile and deformation are explanation of high tool wear and they are predicted through cooling control, and they are better parameters than only hardness control. This research aims to help industry to understand the effects of cooling control after forging process, but it is known that industrial parts have any shapes and sections, so it is important that industry made each correlation between results of this research and how and when is applicable to its own parts.